2004
DOI: 10.1023/b:jice.0000048569.71590.c5
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Right Ventricular Bifocal Pacing in Patients with Permanent Atrial Fibrillation and Severe Dilated Cardiomiopathy Due to Chagas Disease: Three Years of Follow-up

Abstract: The favorable effects of RV bifocal pacing could not be maintained beyond the first 6 months, likely due to the ventricular arrhythmias. Therefore, CRT combined with ICD from the outset may be recommended for this patient group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
2

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 13 publications
1
6
0
2
Order By: Relevance
“…Echocardiography is used in the routine clinical evaluation of CCM patients to assess disease progression, in survival studies 31,32,34,38,[57][58][59][60] to rule out the presence of intraventricular thrombus, 29,34 in the follow-up of pacemakers devices 61 and implanted automatic cardioverter-defibrillators, 62 and to monitor response to vasodilator therapy in patients with HF (enalapril) 63 or to antiparasitic medications (benznidazole), 64 among others. The last study showed in a long-term follow-up that the only independent predictors of deteriorating clinical status were a lower echocardiographic LVEF and a higher LV end-diastolic diameter.…”
Section: Applications In the Management Of Patientsmentioning
confidence: 99%
“…Echocardiography is used in the routine clinical evaluation of CCM patients to assess disease progression, in survival studies 31,32,34,38,[57][58][59][60] to rule out the presence of intraventricular thrombus, 29,34 in the follow-up of pacemakers devices 61 and implanted automatic cardioverter-defibrillators, 62 and to monitor response to vasodilator therapy in patients with HF (enalapril) 63 or to antiparasitic medications (benznidazole), 64 among others. The last study showed in a long-term follow-up that the only independent predictors of deteriorating clinical status were a lower echocardiographic LVEF and a higher LV end-diastolic diameter.…”
Section: Applications In the Management Of Patientsmentioning
confidence: 99%
“…Pacing at virtually any ventricular site changes the natural pattern of activation and contraction sequence because the electrical wave front takes place more slowly through ventricular myocardium than through the His‐Purkinje system. Experimental and clinical studies have evaluated alternative ventricular pacing sites, like RV outflow tract (RVOT), mid‐septum (MS), His bundle, dual‐site RV, LV, and biventricular (BIV) 7–12 . The efficacy and benefit of alternative RV pacing sites are still controversial because previous studies evaluated acute and not chronic effects and were limited by evaluation of only a few patients with low ejection fraction (LEF) 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Several non-randomised long-term studies in CRT candidates, including single case reports, suggest that bifocal RV pacing may yield a sustained haemodynamic benefit with improvement in LV function 15 16. O’Donnell et al implanted a bifocal RV lead system when lateral LV pacing could not be achieved in 50 consecutive CRT candidates who were followed up for 12 months 15.…”
Section: Monochamber LV Pacingmentioning
confidence: 99%